PENGARUH KOMUNIKASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN HOTEL HORISON ULTIMA PALEMBANG - Nina Fitriana; Muchlis Fahmi; Rizka Oktaviani (JURNAL KOMPETITIF, 2019)
ABSTRACT                This study aims to analyze the effect of communication, motivation, and work environment on the employee performance of Palembang Horizon Ultima Hotel. Data used are primary data obtained from employees of Palembang Horison Ultima Hotel as big as 50 respondents. Based on multiple linear regression analysis Y = 0.031 + 0.875X1 + 0,375X2 + 0,061X3 that each increase in the influence of communication by 1 percent will result in an increase in employee performance by 0.875 percent. Increasing the influence of motivation by 1 percent will result in an increase in employee performance by 0.375 percent and each increase in the influence of the work environment by 1 percent will improve employee performance by 0.061 percent. Determination coefficient of adjusted R Square value of 0.951 (95.1%). This means that Communication, Motivation and Influential Work Environment Against Employee Work Performance of Ultima Horison Palembang Hotel is 0.951 or 95.1%, while the remaining 4.9% is influenced by other variables not examined in this study. Correlation coefficient of 0.977 explains that the influence of communication, motivation and work environment on performance is very strong. Keywords: Communication, Motivation, Work Environment, Performance